Design and Implementation of PID Controller in Programmable Logic Controller for DC Motor Position Control of the Conveyor System - M. S., Najib; M. S., Jadin; Raja Mohd Taufika, Raja Ismail; Mohd Rusllim, Mohamed (2007)
Direct Current (DC) motor position control using Programmable Logic Controller (PLC) is one of the applications which are widely used in automation industries. The aim of this project is to implement a Proportional Integral Derivative (PID) controller in a DC motor control system of The Conveyor System. The project is consists of two stages, classical controller and PID controller. The classical controller and PID controller were implemented in PLC and the results of both methods were compared. The system response of both controllers were compared and analyzed. Throughout the analysis, the PID control system illustrated better performance as compared to the classical control system controller in DC motor position control.